Reimplantation after Periprosthetic Joint Infection: The Role of Microbiology - Virginia Suardi; Nicola Logoluso; Filippo Maria Anghilieri; Giuseppe Santoro; Antonio Virgilio Pellegrini (MDPI AG, 2022)
Periprosthetic joint infection (PJI) is among the most feared orthopedic complications. Critical questions are whether the infection is completely resolved before reimplantation and what the clinical significance of positive culture is at reimplantation. The aim of this study was to determine whether a correlation exits between culture results at reimplantation after spacer insertion for hip and knee PJI and treatment failure rate. The data of 84 patients who underwent two-stage exchange arthroplasty for hip or knee PJI were reviewed and the results of intraoperative culture at reimplantation were analyzed quantitatively and qualitatively. Correlations were sought between these patterns and treatment outcome. Our data indicate no evidence for a correlation between positive culture at reimplantation and greater risk of treatment failure. Nonetheless, we noted a higher, albeit statistically not significant rate of treatment failure in patients with at least two samples testing positive. The role of microbiology at reimplantation remains unclear, but a positive culture might signal increased risk for subsequent implant failure. Further studies are needed to elucidate the implications of this finding.